Impact of body mass index on free DIEP flap breast reconstruction: A multicenter cohort study. Issue 8 (August 2021) - Heidekrueger, P.I.; Fritschen, Uv.; Moellhoff, N.; Germann, G.; Giunta, R.E.; Zeman, F.; Prantl, L.
Summary: Introduction: Several patient-related factors have been identified with regard to the safety and efficacy of breast reconstructions. This study analyzed the largest series of microsurgical breast reconstructions in Germany using deep inferior epigastric perforator (DIEP) flaps, with a focus on the impact of patient body mass index (BMI). Patients and methods: A total of 3911 female patients underwent 4561 free DIEP flap breast reconstructions across 22 different centers. The cases were divided into five groups using World Health Organization BMI criteria: underweight group (BMI <18.5 kg/m 2 ), normal weight/ control group (BMI: 18.5–24.9 kg/m 2 ), overweight group (BMI: 25–29.9 kg/m 2 ), moderately obese group (BMI: 30–34.9 kg/m 2 ), and severely obese group (BMI ≥ 35 kg/m 2 ). Surgical complications were accounted for and the five BMI groups were then compared. Results: Overall, there was no significant difference regarding the rate of partial- and total flap loss between all BMI groups ( p > 0.05). However, overweight and obese patients showed significantly higher rates of postoperative infections at the donor and recipient sites than the control group (donor site infections: overweight 0.6%; moderately obese 0.9%; severely obese 2.4% vs control 0.1%; all p <0.01; recipient site infections: overweight 0.5%; moderately obese 0.8%; severely obese 1.4% vs control 0.1%; all p < 0.05). The rate of medical complications also differed significantly between groups, with the highest rates in moderately and severely obese women (moderately obese: 8.4%; severely obese: 13.0% vs. control: 5.1%; p < 0.01). Conclusion: Our findings suggest that successful free tissue transfer can be achieved even in an underweight and severely obese population with acceptable risk for complications.